Insights into the dynamics of methicillin-resistant staphylococci in animals : a focus on Staphylococcus pseudintermedius in dogs - Couto, Natacha (2016)
Tese especialmente elaborada para a obtenção do grau de Doutor em Ciências Veterinárias, especialidade de Clínica